Regulating Private Military and Security Companies: Weaknesses and Promises of Existing International Legal Framework: Addressing the Challenges of Regulating Private Military and Security Companies (Journal of Advances and Scholarly Researches in Allied Education, 2019)
PMSCs are manifesting themselves everywhere. After remaining underground for one hundred-fifty years, the business of private military has returned in just two decades, and without any matter of surprise is growing at an alarming rate. Because of their efficiency, availability of manpower and resources, War Futurists are of the opinion that PMSCs are going to bury the conventional system of war. The problem with their status arises, when it becomes difficult to define when and what services they cancannot provide also with the jurisdictional aspect as well. Indeed, it is not a lawless field, there exists few self-regulations for them, but they have their own restrictions. The draft PMSCs convention has also failed to be executed. In this article, I argue that a comprehensive regulation which takes into consideration all the self-regulating documents and the draft PMSCs convention is the need of the hour.